Heroes and villains : creating national history in contemporary Ukraine - Marples, David R. (Central European University Press, 2007)
Although the main target of this book is the academic community, it will also engender debate in the media, especially in Ukraine itself. Marples examines the sensitive issue of the changing perspectives often shifting 180 degrees on several events discussed in the new narratives of the Stalin years published in the Ukraine since the late Gorbachev period until 2005. These events were pivotal to Ukrainian history in the 20th century, including the Famine of 1932-33 and Ukrainian insurgency during the war years. This latter period is particularly disputed, with regard to the roles of the OUN (Organization of Ukrainian Nationalists) and the UPA (Ukrainian Insurgent Army) during and after the war. Were these organizations "freedom fighters" or "collaborators"? To what extent they constitute, are they the architects of the modern independent state? The main sources are a wide selection of newspapers, journals, monographs, and school textbooks from different regions of the country.